The Impact of CNY Real Exchange Rate on China's Bilateral Trade with the U.S - Huang, Yuan (2012)
This thesis uses Co-integration Test and Error Correction Model to investigate the effect of CNY real exchange rate on China’s bilateral trade with the U.S. The model utilizes China and U.S economic variables, namely, bilateral trade balance, CNY real exchange rate, and GDP. The sample data is from 2005.Q1 to 2011.Q4. The major results suggest that GDP for the U.S plays an important role in China’s bilateral trade to U.S. GDP for China and CNY real exchange rate have limited effect on China’s bilateral trade to U.S.